A Communication Skills Training Workshop to Improve ICU Team Relational Coordination about Goals of Care: A Pilot Study. (October 2022) - Fettig, Lyle; Tang, Qing; Newton, Erin; Rosario, Rafael; Matthias, Marianne S.; Torke, Alexia M.
Background: Families of critically ill patients and their healthcare team must make life and death decisions together. Ideally, intensive care unit team members collaborate in the support of patients and families as goals of care are clarified and care plans are created. Few interventions exist to improve collaboration around this process. Team-based communication skills training about goals-of-care conversations represents one promising intervention.Objective: The purpose of this study was to examine the impact of a communication skills training workshop on coordination and collaboration among ICU team members.Design: Participants from a single institution completed surveys immediately before and six months after completion of the workshop. All participants, including nurses, physicians, social workers, and chaplains, completed a goals-of-care Relational Coordination survey. Nurses and physicians completed a Jefferson Scale of Attitudes Toward Physician-Nurse Collaboration (JSAPNC) survey.Results: Thirty-six participants were enrolled in three workshops. Seventeen and fifteen participants completed the relational coordination survey and JSAPNC respectively at both time points. The mean intergroup relational coordination index increased from 2.94 pre-intervention to 3.19 6-month post ( P = .002, d= .89). Nurse relational coordination index ratings of all other groups increased from 2.84 pre-intervention to 3.08 6-month post ( p = .004, d= 1.23). Mean total scores on the JSAPNC survey did not change significantly from pre-intervention (53.8) to 6-month post (54.2, P = .45).Conclusion: Team-based communication skills training may improve ICU team relational coordination surrounding goals of care.